Phenogenetic profile and agronomic contribution of Azospirillum argentinense Az39T, a reference strain for the South American inoculant industry - Maroniche, Guillermo Andrés (2024)
Azospirillum sp. is a plant growth-promoting rhizobacteria largely recognized for its potential to increase the yield of different important crops. In this work, we present a thorough genomic and phenotypic analysis of A. argentinense Az39T to provide new insights into the beneficial mechanisms of this microorganism. Phenotypic analyses revealed the following in vitro abilities: growth at 20–38 °C (optimum, 28 °C), pH 6.0–8.0 (optimum, pH 6.8), and in the presence of 1% (w/v) NaCl; production of variable amounts of PHB as intracellular granules; nitrogen fixation under microaerophilic conditions; IAA synthesis in the presence of l-tryptophan. Through biochemical (API 20NE) and carbon utilization profiling (Biolog) assays, we proved that A. argentinense Az39T is able to use 15 substrates and metabolize 19 different carbon substrates. Lipid composition indicated a predominance of medium and long-chain saturated fatty acids. A total of 6 replicons classified as one main chromosome, three chromids, and two plasmids, according to their tRNA and core essential genes contents, were identified. Az39T genome includes genes associated with multiple plant growth-promoting (PGP) traits such as nitrogen fixation and production of auxins, cytokinin, abscisic acid, ethylene, and polyamines. In addition, Az39T genome harbor genetic elements associated with physiological features that facilitate its survival in the soil and competence for rhizospheric colonization; this includes motility, secretion system, and quorum sensing genetic determinants. A metadata analysis of Az39T agronomic performance in the pampas region, Argentina, demonstrated significant grain yield increases in wheat and maize, proving its potential to provide better growth conditions for dryland cereals. In conclusion, our data provide a detailed insight into the metabolic profile of A. argentinense Az39T, the strain most widely used to formulate non-legume inoculants in Argentina, and allow a better understanding of the mechanisms behind its field performance.